2011
DOI: 10.4161/cbt.11.2.14624
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of sphingolipid metabolism in cancer

Abstract: Altered sphingolipid metabolism contributes to cancer progression and presents an exploitable target for the development of novel chemotherapeutics. Bioactive sphingolipid metabolites also have the potential to serve as vital biomarkers for cancer and be utilized to determine disease progression, as well as guide therapeutic regimens. Moreover, identification of these sphingolipid biomarkers is achievable based on recent technological advances in sphingolipidomics, which have aided in detection of sphingolipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
188
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(195 citation statements)
references
References 145 publications
6
188
0
1
Order By: Relevance
“…In addition, SM species were observed to be inconsistently altered. Dysregulation in sphingolipid homeostasis has been recognized to contribute to cancer pathogenesis [9,[38][39][40], and its modulation has merged as a potential target for anticancer therapy [41,42].…”
Section: Application In Study Of Hepatocellular Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, SM species were observed to be inconsistently altered. Dysregulation in sphingolipid homeostasis has been recognized to contribute to cancer pathogenesis [9,[38][39][40], and its modulation has merged as a potential target for anticancer therapy [41,42].…”
Section: Application In Study Of Hepatocellular Carcinomamentioning
confidence: 99%
“…Cer, ceramide; dHCer, dihydroceramide; SM, sphingomyelin; HexCer, hexosylceramide; LacCer, lactosylceramide. diabetes, cardiovascular disease, and various cancer diseases as well as central nervous system diseases [7][8][9][10]. To expand our knowledge of this lipid family, development of sensitive, robust and structural-specific methods enabling fast determination of as many sphingolipid species as possible are required.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of complex II, for example, it was demonstrated that during ischaemia/reperfusion, superoxides can induce a loss of SDHA glutathionylation favouring its nitration by peroxynitrite on tyrosine residues, leading to an impairment of its activity (Chen et al, 2007b(Chen et al, , 2008. Finally, besides ROS, pH, calcium, other second messengers frequently misregulated in cancer were shown to control the RC, notably nitric oxide and ceramide, a sphingolipid involved in mitochondrial apoptotic signalling and in the response to anticancer agents (Siskind, 2005;Ryland et al, 2011) (Table 1).…”
mentioning
confidence: 99%
“…A good candidate to make the link between defective RCC function and apoptosis are ROS, as they are often formed when RCCs are partially inhibited. These ROS, which can also be generated in physiological conditions, are (Clementi et al, 1998;Fiorucci et al, 2004) (3) Ceramide synthesis: or depending on cancer type (Ryland et al, 2011) Direct RCC III inhibition and subsequent ROS production (Gudz et al, 1997;Di Paola et al, 2000) Abbreviations: NO, nitric oxide; O 2 , oxygen; RCC, respiratory chain complex; ROS, reactive oxygen species.…”
mentioning
confidence: 99%
“…4,5 Physiological levels of circulating S1P are vasculoprotective, whereas abnormal activation of SphK/S1P signaling is associated with diseases such as cancer, fibrosis, diabetes, and hypertension. [6][7][8][9][10] At high cellular or tissue levels, S1P is a proproliferative, antiapoptotic, promigratory, profibrotic, and proinflammatory signaling molecule. 11 SphK activity and S1P production are stimulated by numerous signals, including growth factors, cytokines, mitogens, and G protein-coupled receptor agonists.…”
mentioning
confidence: 99%